The Genetics of Response to and Side Effects of Lithium Treatment in Bipolar Disorder: Future Research Perspectives - Senner, Fanny; Kohshour, Mojtaba Oraki; Abdalla, Safa; Papiol, Sergi; Schulze, Thomas G. (Frontiers in Pharmacology, 2021)
Although the mood stabilizer lithium is a first-line treatment in bipolar disorder, a substantial number of patients do not benefit from it and experience side effects. No clinical tool is available for predicting lithium response or the occurrence of side effects in everyday clinical practice. Multiple genetic research efforts have been performed in this field because lithium response and side effects are considered to be multifactorial endophenotypes. Available results from linkage and segregation, candidate-gene, and genome-wide association studies (GWASs) indicate a role of genetic factors in determining response and side effects. For example, candidate-gene studies often report GSK3β, BDNF, and SLC6A4 as being involved in lithium response, and the latest GWAS found a genome-wide significant association of treatment response with a locus on chromosome 21 coding for 2 long non-coding RNAs. Although research results are promising, they are limited mainly by a lack of replicability and, despite the collaboration of consortia, insufficient sample sizes. The need for larger sample sizes and “multi-omics” approaches is apparent, and such approaches are crucial for choosing the best treatment options for patients with bipolar disorder. In this article, we delineate the mechanisms of action of lithium and summarize the results of genetic research on lithium response and side effects.